PERBEDAAN HASIL BELAJAR EKONOMI SISWA YANG MENGGUNAKAN STRATEGI LEARNING STARS WITH A QUESTION (LSQ) DENGAN STRATEGI EKSPOSITORI SISWA KELAS XI IPS SMA N 1 MUARO BUNGO JAMBI - Roida Ira, Marta; Akhirmen, M.Si, Drs.; Ramayani, S.Pd,ME, Citra (Pendidikan Ekonomi, 2014)
ABSTRACTthis research based by low result of economy learner. That cause by some factors, the factors such as method which teacher still used teacher center, the studens less involve in teaching learning and value which used result of value not process of value. The goal of this research is for looking different result if learner student used strategy Learning Start With A Question which strategy Ekspositori at SMA N 1 Muara Bungo, Jambi. Kind of this result is experimental of research and interpretation sample technique that used is purposive sampling. Population of all the student grade XI IPS Â SMA N 1 Muara Bungo, was chosen as the experimental class is the class XI IPS1 and XI IPS2 Control class. Analysis data of technique which use by Z experimental because of data normal distribution and group of data has variation that homogen. The result of experiment showed average result of learning experiment class is 76,17 which standar deviassi is 9,37 while the average class control is 69,73 which standart deviasi 10,59. Based analysis data which got, Zhitung (2,362) > Ztabel (1,950) so that the found is H0 regected an H1 accepted. So that conclude there are different the result student used strategy Learning Start With A Question with strategy Ekspositori.